Risk Management for 4-H Youth Development Work - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2010)
4H10.1, a 3-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, serves as the introduction to the Risk Management for 4-H Youth Development Work series. It defines risk management and explains how to incorporate a risk management plan into 4-H activities. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.